SMART CONTRACTS IN ESG REPORTING: A FINTECH-BASED FRAMEWORK FOR ENHANCING CORPORATE GOVERNANCE TRANSPARENCY (Lex localis - Journal of Local Self-Government, 2025)
Environmental, Social, and Governance (ESG) reporting has emerged as a cornerstone of sustainable corporate governance, yet existing disclosure mechanisms remain fragmented, prone to subjectivity, and often criticized for greenwashing. Traditional ESG reports suffer from inconsistent standards, delayed verification, and limited stakeholder trust. This study proposes a fintech-driven framework leveraging smart contracts on blockchain to transform ESG reporting into an automated, transparent, and tamper-proof process. Drawing from a systematic review of existing ESG disclosure practices and fintech applications in governance, the paper outlines how smart contracts can encode reporting obligations, automatically validate sustainability indicators, and provide immutable audit trails. The framework emphasizes three dimensions: (i) automation, where ESG metrics such as carbon footprint, labor diversity, and compliance records are directly linked to predefined smart contract logic; (ii) transparency, as blockchain ensures real-time accessibility and verification for regulators, investors, and stakeholders; and (iii) accountability, by reducing information asymmetry and minimizing risks of manipulation in corporate disclosures. Comparative analysis of traditional vs. blockchain-based ESG systems demonstrates superior efficiency, reliability, and regulatory alignment when smart contracts are deployed. Findings suggest that adopting this fintech-based approach can significantly enhance corporate governance transparency, strengthen investor confidence, and support global sustainability objectives. The study contributes to the growing literature on digital governance by offering a scalable model that integrates ESG reporting, blockchain infrastructure, and policy oversight.